Pursed lips breathing on heart rate and breathing patterns in bronchial asthma patients - Sutrisno, Sutrisno; P.S, Ayuk; S.D, Mayta (Institute of Computer Science (IOCS), 2024)
Bronchial asthma is an inflammatory disease of the respiratory tract and disrupts air flow to the lungs. The aim of this study was to determine the effect of pursed lips breathing on the heart rate and breathing patterns of bronchial asthma patients. Pre-Experimental research design using a Pre-Test and Post-Test approach. The population of all bronchial asthma patients in the Cendana Room at Kediri District Hospital is 30 people, using the Accidental Sampling technique, a sample of 18 respondents was obtained. Statistical tests use the Paired Test. This independent variable is Pursed lips breathing therapy, while the dependent variable is the heart rate and breathing patterns of patients with bronchial asthma. The results of the study showed that there was a decrease in breathing frequency and heart rate in respondents after being given pursed lip breathing treatment. The statistical test results of the intervention on breathing patterns and heart rate showed a p value: 0.000, which means there was a significant influence between before and after treatment. After implementing pursed lips breathing, it was found that there was a decrease in breathing patterns and heart rate, this was due to an increase in lung volume capacity and strengthening of respiratory muscles.